2021
DOI: 10.3390/pharmaceutics13040589
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Single-Chained Surfactants with a Functional Group at the End of the Hydrophobic Tail DNA Compacting Efficiency

Abstract: The interaction between calf-thymus DNA, ctDNA, and various single-chained surfactants with different functional groups at the end of hydrophobic tail was studied with the goal of investigating the influence of the functional group nature on surfactant DNA compacting efficiency. The surfactants investigated were dodecyltriethylammonium bromide (DTEABr), triethyl(1-phenoxydodecyl)ammonium bromide (12PhBr), triethyl(2-naphthoxydodecyl)ammonium bromide (12NBr) and 11-(isonicotinoyloxy)-N,N,N-triethyl-1-undecanami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Their cationic charge mediates strong electrostatic interactions with the negative charges of nucleic acids, giving rise to the formation of CL-NA complexes (often called lipoplexes) [ 23 , 25 , 26 , 27 ]. These complexes adopt internal nanostructures of lamellar, hexagonal or cubic bicontinuous symmetry, with lipid membranes embedding the nucleic acids [ 24 , 25 , 28 , 29 , 30 , 31 ]. By manipulation of the cationic-to-anionic charge ratio, CR (+/−), between liposomes and nucleic acids, as well as adjusting the lipid membrane charge density [ 32 , 33 ], level of PEGylation [ 34 , 35 ], and inclusion of stimuli-responsive or targeting functionalization [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], these particles can be made highly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Their cationic charge mediates strong electrostatic interactions with the negative charges of nucleic acids, giving rise to the formation of CL-NA complexes (often called lipoplexes) [ 23 , 25 , 26 , 27 ]. These complexes adopt internal nanostructures of lamellar, hexagonal or cubic bicontinuous symmetry, with lipid membranes embedding the nucleic acids [ 24 , 25 , 28 , 29 , 30 , 31 ]. By manipulation of the cationic-to-anionic charge ratio, CR (+/−), between liposomes and nucleic acids, as well as adjusting the lipid membrane charge density [ 32 , 33 ], level of PEGylation [ 34 , 35 ], and inclusion of stimuli-responsive or targeting functionalization [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ], these particles can be made highly efficient.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a smaller quantity of gold nanoparticles was needed to obtain similar results, which demonstrates the advantage of using gemini surfactant-covered gold nanoparticles from an economic point of view, as well as for the transport of the drug to the cell and subsequent effective release driven by biopolymer decompaction. Note that the effect of gold nanoparticles covered with 16-Ph-16 gemini surfactants is again noteworthy compared with the analogous DNA–16-Ph-16 system in the absence of any added gold [ 39 , 62 ], in which a surfactant–DNA concentration ratio of 5–10 was needed for the decompaction of the biomolecule, demonstrating the advantage of the new design based on gold nanoparticles. Finally, when the morphology of DNA structures at higher C Au@16-Ph-16 and R ratio was explored, it was observed that the Au@16-Ph-16/DNA–Doxo compacted complexes formed at low R undergo a change in conformation, which is compatible with an increase in the ellipticity of both positive and negative CD bands (see Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…46 To this end, we designed two pH-sensitive PEG-lipid derivatives bearing oleic acid, which has an aliphatic chain similar to the lipids commonly used to prepare lipid nanoparticles. 53 These derivatives vary in spacing (C 2 or C 3 ) between the pH-cleavable bond and the lipid chain (Scheme 1), as the spacer length has been reported to affect the stability of the pH-sensitive bond, 46 thus allowing to tune the pH-lability of the compound.…”
Section: Resultsmentioning
confidence: 99%